Lithium ion battery
By setting up protruding and recessed structures on the positive electrode sheet of the lithium-ion battery and adding specific compounds to the electrolyte, the bottleneck of fast charging and safety performance improvement of lithium-ion batteries is solved, and more efficient lithium-ion embedding and electrolyte are achieved. Infiltrates, improves the fast charging and circulation performance of the battery.
Patent Information
- Application Number
- CN202411708035.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2024-12-27
AI Technical Summary
There are bottlenecks in improving fast charging performance and safety performance of existing lithium-ion batteries, especially the limited innovation in the pole plate structure design and material end.
The first protrusion on one side surface and the corresponding first depression on the other side surface are provided on the positive electrode sheet of the lithium-ion battery, and a specific compound A is added to the electrolyte to adjust its mass ratio, and at the same time, a negative electrode sheet is provided on the negative electrode sheet. The second recess is used to optimize the structure and improve the embedded rate of lithium ions and the wetting property of the electrolyte.
By adjusting the projection area of the projection part on the positive electrode sheet and the proportion of compound A in the electrolyte, the deintercalation rate and safety performance of lithium ions are improved; a recess is provided on the negative electrode sheet to increase the lithium embedded channel, and the circulation and safety performance are improved; Compound B is added to the electrolyte to form a low-impedance SEI film, further improving fast charging and safety performance.
Smart Images

Figure CN119208703A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a lithium ion battery. Background Art
[0002] With the rapid development of lithium-ion battery technology, people have put forward higher requirements for the fast charging performance and safety performance of lithium-ion batteries. To improve battery performance, on the one hand, the positive and negative electrode materials, electrolyte types, diaphragm types and other materials that constitute lithium batteries are optimized and innovated. However, due to the limitations of development and innovation on the material side, improvements in this area have encountered bottlenecks; on the other hand, the design and optimization of the pole piece structure is also crucial to improving battery performance. Therefore, it is of great significance to optimize the pole piece structure to improve battery performance. Summary of the invention
[0003] The purpose of the present invention is to overcome the above-mentioned problems existing in the prior art and to provide a lithium-ion battery, in which a first protrusion is arranged on one surface of the positive electrode sheet and a corresponding first recessed portion is arranged on the other surface of the positive electrode sheet. By controlling the ratio of the total projected area of the first protrusion on the positive electrode sheet to the unit area and adding a specific content of compound A to the electrolyte, the fast charging performance and safety performance of the battery can be improved.
[0004] In order to achieve the above object, the present invention provides a lithium ion battery, the battery comprising a positive electrode sheet, a negative electrode sheet and an electrolyte; In the thickness direction of the positive electrode sheet, the positive electrode sheet includes a first surface and a second surface arranged opposite to each other, the first surface is provided with a plurality of first protrusions at intervals, and the second surface is provided with a plurality of first recessed portions corresponding to the first protrusions; within a unit area of 1 cm×1 cm, the ratio of the total projection area of the first protrusions on the positive electrode sheet to the unit area is recorded as m%; m satisfies: 3≤m≤60; The electrolyte includes compound A, and the mass proportion of compound A is denoted as a% based on the total mass of the electrolyte; a satisfies: 5≤a≤70; The chemical formula of the compound A is shown in Formula I: (Formula I), Wherein, R1, R2, R3, R4, R5, R6, and R7 are independently selected from at least one of H, halogen-substituted or unsubstituted C1-C6 alkyl, halogen-substituted or unsubstituted C3-C6 cycloalkyl, halogen-substituted or unsubstituted C1-C6 alkoxy, halogen-substituted or unsubstituted C2-C6 alkenyl, and halogen-substituted or unsubstituted C2-C6 alkynyl.
[0005] The present invention adopts the above technical solution to achieve the following beneficial effects: (1) The lithium-ion battery provided by the present invention can improve the wettability of the electrolyte to the positive electrode material, increase the lithium ion deintercalation rate, and improve the fast charging performance and safety performance of the battery by adjusting the ratio of the projected area of the first protrusion on the positive electrode sheet to the unit area and the proportion of compound A in the electrolyte; (2) The lithium-ion battery provided by the present invention can form a low-impedance SEI film by further adding compound B to the electrolyte and adjusting the mass ratio of compound B to a specific range, thereby increasing the insertion rate of lithium ions, further improving the fast charging performance of the battery, and improving the safety performance of the battery; (3) The lithium-ion battery provided by the present invention further provides a second recessed portion in the negative electrode sheet, and adjusts the ratio of the total projected area of the second recessed portion on the single-side surface of the negative electrode sheet to the unit area, thereby increasing the lithium insertion channel of the negative electrode and further improving the battery cycle performance and safety performance.
[0006] The endpoints and any values of the range disclosed in this article are not limited to the precise range or value, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article. Herein, in the absence of special instructions, data ranges include endpoints. BRIEF DESCRIPTION OF THE DRAWINGS
[0007] Figure 1 Shown is a structural schematic diagram of a positive electrode sheet in an embodiment of the present invention.
[0008] Figure 2 The figure shows a partial enlarged schematic diagram of the first recessed portion and the first raised portion in the embodiment of the present invention.
[0009] Figure 3 Shown is a schematic structural diagram of a negative electrode sheet in an embodiment of the present invention.
[0010] Figure numerals: 1, second surface; 2, first surface; 3, first recessed portion; 4, first protruding portion. DETAILED DESCRIPTION
[0011] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.
[0012] Unless otherwise defined, all scientific and technical terms used in the present invention have the same meanings as commonly understood by one of ordinary skill in the art to which the present invention relates.
[0013] In the present invention, the terms "battery", "lithium battery", "lithium-ion battery" and "lithium-ion secondary battery" all have the same meaning and refer to lithium-ion secondary batteries, which generally include an electrode assembly (such as a positive electrode sheet, a negative electrode sheet and a separator), a container (shell) for accommodating the electrode assembly, and an electrolyte.
[0014] In the present invention, the term "halogen" represents fluorine, chlorine, bromine and iodine atoms.
[0015] In the present invention, the term "C1-C6 alkyl" represents a monovalent alkyl group having 1 to 6 carbon atoms, including straight-chain or branched C1-C6 alkyl groups.
[0016] In the present invention, the term "C3-C6 cycloalkyl" represents a saturated carbocyclic group having 3-6 carbon atoms and having a single ring (e.g., cyclohexyl) or multiple condensed rings (e.g., norbornyl). C3-C6 cycloalkyl includes cyclopentyl, cyclohexyl, norbornyl, etc.
[0017] In the present invention, the term "C1-C6 alkoxy" represents a group -OR of 1 to 6 carbon atoms, wherein R includes "alkyl", "aryl", "heteroaryl", "arylalkyl" or "heteroarylalkyl".
[0018] In the present invention, the term "C2-C6 alkenyl" represents an alkenyl group of 2 to 6 carbon atoms, including a straight chain or branched C2-C6 alkenyl group. It can have any available number of double bonds at any available position, and the configuration of the double bond can be (E) or (Z) configuration.
[0019] In the present invention, the term "C2-C6 alkynyl" represents an alkynyl group of 2 to 6 carbon atoms, including a straight chain or branched C2-C6 alkynyl group. It can have any available number of triple bonds at any available position.
[0020] The present invention provides a lithium ion battery, the battery comprising a positive electrode sheet, a negative electrode sheet and an electrolyte; In the thickness direction of the positive electrode sheet, the positive electrode sheet includes a first surface and a second surface arranged opposite to each other, the first surface is provided with a plurality of first protrusions at intervals, and the second surface is provided with a plurality of first recessed portions corresponding to the first protrusions; within a unit area of 1 cm×1 cm, the ratio of the total projection area of the first protrusions on the positive electrode sheet to the unit area is recorded as m%; m satisfies: 3≤m≤60; The electrolyte includes compound A, and the mass proportion of compound A is denoted as a% based on the total mass of the electrolyte; a satisfies: 5≤a≤70; The chemical formula of the compound A is shown in Formula I: (Formula I), Wherein, R1, R2, R3, R4, R5, R6, and R7 are independently selected from at least one of H, halogen-substituted or unsubstituted C1-C6 alkyl, halogen-substituted or unsubstituted C3-C6 cycloalkyl, halogen-substituted or unsubstituted C1-C6 alkoxy, halogen-substituted or unsubstituted C2-C6 alkenyl, and halogen-substituted or unsubstituted C2-C6 alkynyl.
[0021] Exemplarily, the ratio m% of the total projected area of the first protrusion on the positive electrode sheet to the unit area can be, for example, 3%, 5%, 7%, 9%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60% or any point value in the range composed of any two of the above point values, preferably 20%-40%.
[0022] In the present invention, the term "1 cm×1 cm unit area" represents an arbitrary 1 cm×1 cm unit area where a plurality of protrusions and / or a plurality of depressions provided on one side of the positive electrode active material layer surface / negative electrode active material layer surface are located.
[0023] In the present invention, the total projection area of the first protrusions on the positive electrode sheet can be interpreted as: in an arbitrary 1cm×1cm unit area of the positive electrode sheet, in a direction perpendicular to the positive electrode sheet, the sum of the projection areas of several first protrusions in a 1cm×1cm unit area.
[0024] In some embodiments, the ratio of the total projected area of the first recessed portion on the positive electrode sheet to the unit area is 3%-60%.
[0025] The total projection area of the first recessed portions on the positive electrode sheet can be interpreted as: the sum of the projection areas of several first recessed portions within a 1cm×1cm unit area of the positive electrode sheet in a direction perpendicular to the positive electrode sheet within an arbitrary 1cm×1cm unit area of the positive electrode sheet.
[0026] Illustratively, the mass proportion a% of compound A can be, for example, 5%, 8%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 67%, 70%, or any point value in the range consisting of any two of the above point values, preferably 10%-60%.
[0027] The present invention optimizes the structure of the positive electrode sheet, and arranges a first protrusion on one side of the surface of the positive electrode active material layer, and a concave portion corresponding to the protrusion on the other side of the surface. This concave-convex texture increases the specific surface area of the positive electrode, increases the contact area between the positive electrode and the electrolyte, can improve the wettability of the electrolyte to the positive electrode material, and improve the efficiency of the positive electrode lithium ion release. Through the above-mentioned optimization measures for the structure of the positive electrode sheet, a large number of lithium ions are efficiently released from the positive electrode. However, if these lithium ions cannot be quickly embedded in the negative electrode material, they will gather in large quantities on the negative electrode surface, which is likely to cause the formation of dead lithium and lithium dendrites on the negative electrode surface, deteriorating the battery cycle performance. The present invention introduces compound A (chemical formula as shown in formula I) into the electrolyte system. Compound A has a relatively low viscosity (<1 mPa·s; tested at 25°C), so that lithium ions released in large quantities from the positive electrode material can be quickly conducted in the electrolyte, thereby improving the migration rate of the lithium ions. In addition, compound A can construct a multi-coordinated solvation structure with lithium ions, and the steric hindrance between solvent molecules is relatively large, which weakens the force on lithium ions, thereby reducing the desolvation energy barrier of lithium ions, helping lithium ions to be more easily embedded in the negative electrode, reducing the aggregation of lithium ions in and near the protrusions and / or depressions on the surface of the negative electrode, allowing lithium ions to be quickly embedded in the negative electrode material, and reducing the generation of dead lithium and lithium dendrites.
[0028] A first protrusion is provided on one surface of the positive electrode sheet and the projected area of the protrusion is controlled within an appropriate range. Combined with the use of compound A in the electrolyte, the deintercalation rate of lithium ions can be effectively increased, the generation of dead lithium and lithium dendrites can be reduced, the fast charging performance of the battery can be improved, and the safety performance of the battery can be enhanced.
[0029] In some embodiments, the ratio m of the projected area of the first protrusion and / or the first recess on the positive electrode sheet to the unit area satisfies 20≤m≤40. The present invention further satisfies the above range by adjusting m, which can further optimize the lithium ion deintercalation rate and improve the fast charging performance of the battery on the one hand, and reduce the pores and defects between the positive electrode material particles in the positive electrode sheet on the other hand, making the positive electrode sheet structure more uniform, improving the overall strength of the positive electrode material, and effectively avoiding the positive electrode material from being squeezed and causing cracks or breakage due to stress concentration, thereby avoiding the problem of reduced capacity of the positive electrode material and decreased cycle performance, and further improving the cycle performance of the battery.
[0030] In some embodiments, a positive electrode sheet embossing process (eg, roll pressing) may be used to form an embossed pattern, such as Figure 1 and Figure 2As shown, the entire surface of the positive electrode sheet is embossed, and the positive electrode sheet includes a second surface 1 and a first surface 2 that are arranged opposite to each other. After the embossing treatment, a plurality of first recessed portions 3 with uniform intervals are formed on the second surface 1, and a plurality of first raised portions 4 with uniform intervals corresponding to the first recessed portions 3 are formed on the first surface 2. Similarly, a plurality of first recessed portions 3 with uniform intervals can be formed on the first surface 2 after the embossing treatment, and a plurality of first raised portions 4 with uniform intervals corresponding to the first recessed portions 3 can be formed on the second surface 1, that is, the positions of the first raised portions 4 and the first recessed portions 3 in the second surface 1 and the first surface 2 can be interchanged.
[0031] In some other embodiments, the embossing process may be performed only on a local area of the positive electrode sheet, such as an edge area, an arc area, etc.
[0032] In some embodiments, the first raised portion or the first depressed portion (embossed pattern) is a regular or irregular shape, such as a circle, a square, a hexagon, other spliced shapes or an irregular shape, preferably a regular shape, such as a circle.
[0033] In some embodiments, the first protrusions and the first recesses may be arranged in a uniform interval, or the arrangement may be adjusted according to actual needs, such as partially arranged in a uniform interval and partially arranged in a non-uniform interval.
[0034] In some embodiments, the first protrusion and / or the first depression satisfies at least one of the following conditions: (a) The height of the first protrusion (denoted as H1) is 3 μm-40 μm, for example, 3 μm, 4 μm, 5 μm, 6 μm, 8 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm or any point value in the range of any two of the above points; and / or, the depth of the first recess (denoted as H2) is 3 μm-40 μm, for example, 3 μm, 4 μm, 5 μm, 6 μm, 8 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm. The "height of the first protrusion" can be interpreted as the maximum vertical distance from the top of the first protrusion away from the positive electrode current collector to the first surface of the positive electrode sheet, such as Figure 2 As shown in H1; the “depth of the first recessed portion” can be interpreted as the maximum vertical distance from the bottom end of the first recessed portion close to the positive electrode current collector to the second surface of the positive electrode sheet, such as Figure 2When the height of the first protrusion and the depth of the first recess meet the above range, it can avoid the situation that the height of the first protrusion is too high or the depth of the first recess is too deep, which makes the protrusion structure fragile and easy to be broken by mechanical extrusion and wear; it can also avoid the situation that the height of the first protrusion is too low or the depth of the first recess is too shallow, the electrolyte cannot well infiltrate the inside of the pole piece, and the fast charging performance of the battery is not significantly improved.
[0035] (b) The diameter of the first protrusion (denoted as R1) is 0.2 mm-8 mm, for example, it can be 0.2 mm, 0.5 mm, 0.6 mm, 0.8 mm, 1 mm, 2 mm, 3 mm, 4 mm, 5 mm, 6 mm, 7 mm, 8 mm or any point value in the range formed by any two of the above points; and / or, the diameter of the first recessed portion (denoted as R2) is 0.2 mm-8 mm, for example, it can be 0.2 mm, 0.5 mm, 0.6 mm, 0.8 mm, 1 mm, 2 mm, 3 mm, 4 mm, 5 mm, 6 mm, 7 mm, 8 mm or any point value in the range formed by any two of the above points. The "diameter of the first protrusion" and / or the "diameter of the first recessed portion" can be interpreted as the maximum straight-line distance between the two edges of the first protrusion and / or the first recessed portion in the direction parallel to the positive electrode sheet, such as Figure 2 As shown in R1 and R2. When the diameter of the first protrusion and the diameter of the first recess meet the above range, the area of the first protrusion and / or the first recess can be controlled to avoid the diameter being too large. The positive electrode material corresponding to the recess is not subjected to the stress of the positive electrode material, which is easy to deform during the battery cycle, causing the positive electrode material to fall off the collector, resulting in rapid decay of the battery capacity, and the fallen positive electrode material may form a conductive path inside the battery, causing safety problems such as short circuit and thermal runaway; it can also avoid the diameter being too small, the electrolyte cannot well infiltrate the inside of the pole piece, and the improvement of the battery fast charging performance is not obvious.
[0036] (c) The spacing between adjacent first protrusions (denoted as D1) is 0.2 mm-8 mm, for example, 0.2 mm, 0.5 mm, 0.6 mm, 0.8 mm, 1 mm, 2 mm, 3 mm, 4 mm, 5 mm, 6 mm, 7 mm, 8 mm, or any point value in the range of the above two points; and / or, the spacing between adjacent first depressions (denoted as D2) is 0.2 mm-8 mm, for example, 0.2 mm, 0.5 mm, 0.6 mm, 0.8 mm, 1 mm, 2 mm, 3 mm, 4 mm, 5 mm, 6 mm, 7 mm, 8 mm, or any point value in the range of the above two points. The spacing between adjacent first protrusions and the spacing between adjacent first depressions may be the same or different, and are preferably the same. The “distance between adjacent first protrusions” and / or the “distance between adjacent first depressions” can be interpreted as the shortest straight distance between two adjacent first protrusions / first depressions on the surface of the positive electrode sheet in the length direction of the positive electrode sheet, which is recorded as the distance between adjacent first protrusions or the distance between adjacent first depressions, such as Figure 2 As shown in D1 and D2.
[0037] When the spacing between the first protrusions and the spacing between the first recessed portions meet the above range, the arrangement density of the first protrusions and / or the first recessed portions is within an appropriate range, and the number of the first protrusions and / or the first recessed portions is controlled within a certain area, which can not only ensure the effective improvement of the fast charging performance of the battery, but also avoid the problem of unstable positive electrode structure caused by too small spacing.
[0038] When the first protrusion and / or the first recessed portion meets the above conditions, it can better improve the wettability of the electrolyte to the positive electrode material and improve the efficiency of the positive electrode lithium ion extraction; reduce the pores and defects in the positive electrode sheet, make the positive electrode sheet structure more uniform, improve the overall strength of the positive electrode material, reduce stress concentration during expansion, improve the structural stability of the positive electrode sheet, and improve the fast charging cycle performance of the battery.
[0039] In some embodiments, the mass proportion a of compound A satisfies 10≤a≤60; in the process of lithium ions being deintercalated from the electrolyte to the surface of the electrode material, a certain solvation energy barrier needs to be overcome. When the mass proportion of compound A is adjusted by the present invention to further satisfy the above range, compound A can further reduce the lithium ion solvation energy barrier, making it easier for lithium ions to be deintercalated from the electrolyte, accelerating the desolvation process of lithium ions, improving the fast charging performance of the battery, and avoiding thermal runaway of the battery caused by lithium precipitation or dead lithium due to the inability of the negative electrode to quickly intercalate lithium ions, thereby improving the battery safety performance.
[0040] In some embodiments, the compound A comprises at least one of the following compounds: (Formula I-1), (Formula I-2), (Formula I-3), (Formula I-4), (Formula I-5), (Formula I-6), (Formula I-7), (Formula I-8).
[0041] The compound A shown above has a linear chain structure and has a lower viscosity and desolvation energy. Further selection of the above compound A can reduce the viscosity of the electrolyte, which is more conducive to increasing the lithium ion deintercalation rate and improving the fast charging performance and thermal runaway safety of the battery.
[0042] In some embodiments, the electrolyte further includes a compound B, and the compound B includes ethyl difluoroacetate (DFEA).
[0043] The present invention can further add DFEA to the electrolyte, and DFEA can form a low-impedance SEI film containing inorganic LiF on the surface of the negative electrode, reduce the resistance of lithium ions passing through the negative electrode interface, and further promote the insertion rate of lithium ions; in addition, the fluorine atoms in DFEA are tightly combined with carbon atoms to form a stable carbon-fluorine bond, and the strong electronegativity of the fluorine atoms makes the electron cloud densely distributed around the fluorine atoms, thereby enhancing the bond energy of the carbon-fluorine bond, making it less likely to break and undergo oxidation reaction, thereby further improving the fast charging performance and safety of the battery at high voltage.
[0044] In some embodiments, the compound B further comprises at least one of the following compounds: (Formula II-1), (Formula II-2), (Formula II-3), (Formula II-4), (Formula II-5), (Formula II-6), (Formula II-7), (Formula II-8), (Formula II-9), (Formula II-10), (Formula II-11), (Formula II-12), (Formula II-13), (Formula II-14).
[0045] Further selectively adding the compound B shown above can form a more stable low-impedance SEI film, while promoting compound A to form a multi-coordinated solvation structure with lithium ions, significantly increasing the lithium ion embedding rate and improving the fast charging performance and safety performance of the battery.
[0046] In some embodiments, based on the total mass of the electrolyte, the mass proportion of compound B is recorded as b%; b satisfies 5≤b≤25, and the mass proportion of compound B can be, for example, 5%, 6%, 7%, 9%, 11%, 13%, 15%, 17%, 19%, 21%, 23%, 24%, 25% or any point value in the range composed of the above two point values. Compound B is easy to decompose and produce gas under high temperature conditions, which will accelerate the performance degradation of the battery and cause safety problems such as thermal runaway. Therefore, when the mass proportion of compound B is adjusted to meet the above range, the above problems caused by a large amount of compound B added can be reduced, further improving the fast charging performance of the battery and improving the safety of the battery.
[0047] In some embodiments, the mass proportion b of compound B and the mass proportion a of compound A satisfy: 0<a / b≤10, and the value of a / b can be, for example, 0.001, 0.01, 0.1, 0.5, 1, 2, 3, 4, 5, 6, 7, 8, 9, 10 or any point value in the range of the above two point values. The present invention can enhance the solubility of lithium salt in the solvent to a certain extent by adjusting the mass proportion relationship of compound A and compound B in the electrolyte, thereby promoting more lithium ions to form a multi-coordinated solvation structure with compound A, reducing the desolvation energy of lithium ions, making lithium ions easier to embed into the negative electrode, further improving the fast charging performance of the battery, reducing the aggregation of lithium ions on the negative electrode surface and the generation of dead lithium and dendrites in the embossed area, improving the thermal runaway caused by lithium dendrites, and improving the safety performance of the battery. It prevents the overall viscosity of the electrolyte from increasing when a large amount of compound B is added, which in turn reduces the transmission rate of lithium ions in the electrolyte. It also prevents the mass proportion of compound A in the electrolyte from being too large, resulting in the proportion of other components such as lithium salt being too small, affecting the transmission of lithium ions and reducing the fast charging performance of the battery.
[0048] In some embodiments, in the thickness direction of the negative electrode sheet, the negative electrode sheet includes a third surface and a fourth surface arranged opposite to each other, and the third surface and / or the fourth surface are provided with a plurality of second recessed portions; within a unit area of 1 cm×1 cm, the ratio of the total projection area of the second recessed portions on the third surface or the fourth surface to the unit area is recorded as n%; n satisfies: 3≤n≤85, for example, it can be 3%, 5%, 7%, 9%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 82%, 85% or any point value in the range composed of any two of the above point values, preferably 20≤n≤60. Since the first protrusion and the first depression are arranged on the surface of the positive electrode active material layer, the surface area of the positive electrode material is significantly increased, and the lithium de-lithiation channel of lithium ions is also increased accordingly. The present invention can also arrange a second depression on the surface of the negative electrode sheet, thereby optimizing the negative electrode structure, increasing the contact area between the negative electrode material and the electrolyte, increasing the negative electrode lithium insertion channel of lithium ions, further reducing the dead lithium and lithium precipitation caused by the inability of lithium ions released from the positive electrode to be embedded in the negative electrode in time, and improving the battery cycle performance and safety performance.
[0049] In some embodiments, the second recessed portion may be formed by laser drilling or wire punching. Figure 3 As shown in FIG. 1 ), there are only a number of second recessed portions on the third surface and / or the fourth surface of the negative electrode sheet.
[0050] In some embodiments, an embossing process may be used to form an embossed pattern on the negative electrode sheet. For example, the entire surface of the negative electrode sheet may be embossed. Figure 1 The negative electrode sheet includes a third surface and a fourth surface that are arranged opposite to each other. The third surface of the negative electrode sheet is embossed to form a plurality of second recessed portions that are evenly spaced, and the fourth surface is formed with a plurality of second raised portions that are evenly spaced and correspond to the second recessed portions. Similarly, the fourth surface may be embossed to form a plurality of second recessed portions that are evenly spaced, and the third surface may be formed with a plurality of second raised portions that are evenly spaced and correspond to the second recessed portions, that is, the positions of the second raised portions and the second recessed portions in the third and fourth surfaces of the negative electrode sheet may be interchangeable.
[0051] In some other embodiments, the embossing process may be performed only on a local area of the negative electrode sheet, such as an edge area, an arc area, etc.
[0052] In the present invention, the total projection area of the second recessed portions on the negative electrode sheet can be interpreted as: the sum of the projection areas of a plurality of second recessed portions within a unit area of 1 cm×1 cm in any unit area of 1 cm×1 cm of the negative electrode sheet.
[0053] In some embodiments, m and n satisfy: n>m; G=n / m, G satisfies 1≤G≤4, and the value of G can be, for example, 1, 1.5, 2, 2.5, 3, 3.5, 4 or any point value in the range composed of the above two point values. When the ratio of the total projected area of the second recessed portion on the negative electrode sheet to the unit area (n) is adjusted to be greater than the ratio of the total projected area of the first protruding portion on the positive electrode sheet to the unit area (m), more space is provided to accommodate lithium ions during charging, which can prevent lithium ions from gathering on the electrode surface. When the value of G increases, even if the content of lithium ions in the electrolyte is low, it will not cause lithium ion aggregation and lithium dendrite formation on the negative electrode surface, and will not deteriorate the safety performance of the battery; but if the G value is too large (>4), there will be too few convex or concave areas on the positive electrode, and the effect of improving the wettability of the electrolyte to the positive electrode material is not good, and the efficiency of lithium ions coming out of the positive electrode cannot be effectively improved. When G meets the above range, it can take into account both the improvement of the safety performance and the fast charging performance of the battery.
[0054] In some embodiments, G and a satisfy: 50≤a*G≤250, and the value of a*G can be, for example, 50, 52, 54, 56, 58, 60, 70, 80, 90, 100, 120, 140, 160, 180, 200, 220, 240, 242, 244, 246, 248, 250 or any point value in the range of the above two point values. When the value of G is small, the negative electrode may still have the risk of lithium precipitation, and more compound A needs to be added to the electrolyte to improve the lithium ion transmission efficiency, reduce the negative electrode lithium precipitation, and improve the battery charge and discharge performance. G and a further satisfy the above ranges, which can avoid the situation where the lithium ions released from the positive electrode cannot be embedded in the negative electrode in time when a*G<50, causing dead lithium and lithium precipitation, resulting in safety problems such as thermal runaway of the battery; avoid the situation where the mass proportion of compound A in the electrolyte is too large when a*G>250, resulting in too small a proportion of other components such as lithium salt, affecting the transmission of lithium ions, and reducing the fast charging performance of the battery; or the G value is too large, resulting in too few convex or concave areas on the positive electrode, and the effect of improving the wettability of the electrolyte to the positive electrode material is not good, and the efficiency of lithium ions released from the positive electrode cannot be effectively improved; or there are too many convex or concave areas on the negative electrode sheet, and the internal structure of the negative electrode material is damaged, which increases the energy loss of the battery during the charging and discharging process and reduces the cycle life of the battery.
[0055] In some embodiments, the second raised portion or the second recessed portion (embossing pattern) is a regular or irregular shape, such as a circle, a square, a hexagon, other spliced shapes or an irregular shape.
[0056] In some embodiments, the second protrusions and the second recesses may be arranged in a uniform interval, or the arrangement may be adjusted according to actual needs, such as partially arranged in a uniform interval and partially arranged in a non-uniform interval.
[0057] In some embodiments, the second recessed portion satisfies at least one of the following conditions: (i) The width of the second recessed portion is 30 μm-4000 μm, for example, 30 μm, 40 μm, 60 μm, 80 μm, 100 μm, 120 μm, 140 μm, 160 μm, 170 μm, 200 μm, 500 μm, 800 μm, 1000 μm, 1500 μm, 2000 μm, 2500 μm, 3000 μm, 3500 μm, 4000 μm or any value in the range consisting of any two of the above values.
[0058] In some embodiments, when the second recessed portion is provided in the negative electrode sheet by using an embossing process, the width of the second recessed portion can be understood as the "diameter of the second recessed portion", that is, the maximum straight-line distance between the two inner edges of the second recessed portion in a direction parallel to the negative electrode sheet. The diameter of the second recessed portion is 200 μm-4000 μm (0.2 mm-4 mm).
[0059] In some embodiments, when a second recessed portion (linear groove) is provided in the negative electrode sheet by laser or other methods, the maximum straight line distance in the width direction of the linear groove is recorded as the width of the second recessed portion. The width of the second recessed portion is preferably 30 μm-170 μm.
[0060] When the width of the second recessed portion meets the above range, it can avoid the situation where the width of the second recessed portion is too wide, causing the structure of the recessed portion to be fragile and easy to cause structural fragmentation due to mechanical extrusion and wear; it can also avoid the situation where the width of the second recessed portion is too narrow, the electrolyte cannot infiltrate the inside of the electrode well, and the improvement of the battery fast charging performance is not obvious.
[0061] (ii) The depth of the second recessed portion is 5 μm-60 μm, for example, it can be 5 μm, 8 μm, 10 μm, 20 μm, 30 μm, 40 μm, 50 μm, 60 μm or any point value in the range composed of the above two point values. The "depth of the second recessed portion" can be interpreted as the vertical distance from the surface of the negative electrode active material layer to the bottom of the second recessed portion; the second recessed portion does not penetrate the negative electrode current collector. When the depth of the second recessed portion meets the above range, it can avoid the situation where the depth of the second recessed portion is too deep, causing the structure of the recessed portion to be fragile and easy to be broken by mechanical extrusion and wear; it can also avoid the depth of the second recessed portion being too shallow, the electrolyte cannot well infiltrate the inside of the electrode, and the improvement of the battery fast charging performance is not obvious.
[0062] (iii) The spacing between adjacent second recessed portions is 0.2 mm-10 mm, for example, it can be 0.2 mm, 0.3 mm, 0.4 mm, 0.5 mm, 1 mm, 1.5 mm, 2 mm, 2.5 mm, 3 mm, 5 mm, 6 mm, 8 mm, 10 mm or any point value in the range of the above two point values. "The spacing between adjacent second recessed portions" can be interpreted as the shortest straight distance between two adjacent and closest second recessed portions on the surface of the negative electrode sheet in the length direction of the negative electrode sheet, which is recorded as the spacing between adjacent second recessed portions. .
[0063] When the spacing between the second recessed portions meets the above range, the arrangement density of the second recessed portions is within an appropriate range, and the number of the second recessed portions is controlled within a certain area, which can not only ensure the effective improvement of the fast charging performance of the battery, but also avoid the problem of unstable negative electrode sheet structure caused by too small spacing.
[0064] In some embodiments, the second recessed portion is preferably a linear groove, such as Figure 3 shown.
[0065] In the present invention, the structural optimization of the negative electrode sheet is preferably to set only the second recessed portion in the negative electrode active material layer. Such a setting can increase the lithium ion embedding rate and improve the fast charging performance of the battery, while also providing more microspaces to reserve sufficient internal space for the volume expansion of the negative electrode sheet (such as a silicon-containing negative electrode), thereby avoiding the extrusion deformation of the negative electrode sheet caused by the expansion of the negative electrode during a long cycle, lithium precipitation and other safety issues.
[0066] In some embodiments, the electrolyte further comprises a compound C, and the chemical formula of the compound C is shown in Formula III: (Formula III), Wherein, X1, X2, and X3 are independently selected from or , and at least one of X1, X2, and X3 contains an S group, A1, A2, A3, and A4 are independently selected from O, S, or an alkyl group connected to C, and at least one of A3 and A4 contains an O atom.
[0067] It should be noted that the dotted line shown in the chemical formula of compound C (Formula III) represents that the ring structure on the right side of the formula (the ring structure where n3 is located) can replace the H at the C position adjacent to A3 and far away from the X2 group; or when A3 is a C-linked alkyl group, it can also replace the H of the alkyl group at the A3 position.
[0068] The present invention adds compound C to the electrolyte to form a protective film containing sulfide. The protective film has high ionic conductivity and contains micropores or channels in its structure, so that the diffusion barrier of lithium ions in the protective film is further reduced. The good mechanical properties and elasticity of the protective film can promote the uniform deposition of lithium ions, and also inhibit the side reaction caused by direct contact between the electrolyte and the electrode material, inhibit the generation of lithium dendrites, reduce lithium precipitation, and further improve the thermal safety performance of the battery.
[0069] In some embodiments, based on the total mass of the electrolyte, the mass proportion of compound C is recorded as c%, and c satisfies: 0.1≤c≤5. The mass proportion of compound C can be, for example, 0.1%, 0.2%, 0.4%, 0.8%, 1%, 2%, 3%, 4%, 4.4%, 4.8%, 5%, or any point value in the range composed of any two of the above point values; when the mass proportion of compound C further satisfies the above range, it can be avoided that when c<0.1%, the protective film formed by compound C is too thin and uneven, and the cycle and thermal stability of the lithium-ion battery are not significantly improved; it can also be avoided that when c>5%, the protective film formed by the compound C is too thick, resulting in excessive impedance of the battery, deteriorating the charging lithium deposition window and cycle life of the battery.
[0070] Preferably, the compound C comprises at least one of the following compounds: (Formula III-1), (Formula III-2), (Formula III-3), (Formula III-4), (Formula III-5), (Formula III-6), (Formula III-7), (Formula III-8), (III-9).
[0071] In some embodiments, the negative electrode sheet includes a negative electrode active material, and the negative electrode active material includes a silicon-carbon material; in the negative electrode active material, the content of silicon element accounts for 0.01%-70%, for example, it can be 0.01%, 0.05%, 0.1%, 0.5%, 1%, 5%, 10%, 20%, 30%, 40%, 50%, 60%, 65%, 70% or any point value in the range composed of any two of the above point values; when silicon-carbon material is used in the negative electrode active material and the content of silicon element is adjusted to meet the above range, it can ensure that the battery has good thermal safety performance and cycle life, so that the negative electrode material has a higher lithium storage capacity, and the energy density of the lithium-ion battery is further improved. At the same time, when the content of silicon element accounts for too large a proportion, the volume change of the silicon-containing negative electrode material during the charge and discharge process is more significant, resulting in the crushing of the negative electrode material particles, the separation of the active substance and the current collector, and the formation of an unstable SEI film. The rupture of the SEI film will lead to the continuous consumption of the electrolyte, thereby greatly affecting the cycle stability and performance of the battery.
[0072] The test method for the silicon content ratio can be tested by thermogravimetric analysis, for example, using a Shimadzu DTG-60 thermogravimetric analyzer for testing, and the test conditions include: sample weight 5 mg, air as atmosphere, heating rate 10°C / min from room temperature to 900°C and constant temperature for 40 min. The relationship between the mass ratio of silicon-carbon material (denoted as x) and the final weight residual percentage of the entire test (denoted as y) is: x=7y / 15.
[0073] Preferably, the silicon-carbon material satisfies at least one of the following conditions: 1) The Dv50 of the silicon-carbon material is 5 μm-15 μm, for example, it can be 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm or any point value in the range of the above two points. The Dv50 of the silicon-carbon material meets the above range, which can optimize the electrode structure of the silicon-carbon composite material, reduce the volume expansion under the high-voltage system, help reduce the silicon-carbon composite stress of the material, optimize the lithium ion transmission rate and structural stability, and avoid the increase of the mechanical stress of the silicon material when the silicon-carbon material particle size is too small, which is not conducive to the structural stability of the silicon-carbon material, causing the SEI film to be damaged, the side reaction to be aggravated, the SEI to grow and thicken repeatedly, the impedance to deteriorate, and the electrolyte to be quickly consumed, which worsens the cycle life of the battery; it can also avoid the silicon-carbon material when the particle size is too large, and the silicon-carbon material will produce more drastic volume changes during the charge and discharge process, resulting in the internal stress concentration of the silicon-carbon material, resulting in the silicon-carbon material being broken or even pulverized.
[0074] 2) The specific surface area of silicon carbon material is 0.3 m 2 / g-15 m 2 / g, for example, 0.3 m 2 / g, 0.6 m 2 / g, 0.9m 2 / g, 1 m 2 / g, 1.5 m 2 / g, 2 m 2 / g, 3 m 2 / g, 4 m 2 / g, 5 m 2 / g, 6 m 2 / g, 7 m 2 / g, 8 m 2 / g, 9 m 2 / g, 10m 2 / g, 11 m 2 / g, 12 m 2 / g, 13 m 2 / g, 14 m 2 / g, 15 m 2 / g or any point value in the range formed by the above two point values. When the specific surface area of the silicon-carbon material meets the above range, the electrolyte infiltration contact area can be increased, and the number of reactive active sites can be increased. At the same time, it can avoid that the specific surface area is too small, the active sites on the surface of the material are reduced, and the interaction with other substances (such as reactants, solvents, etc.) is weakened, thereby reducing the reactive activity; when the specific surface area is too large, the silicon-carbon material has more pores and defects, which makes the material easy to deform or rupture when subjected to stress or high temperature.
[0075] 3) The sphericity of the silicon-carbon material is 0.8-1, for example, it can be 0.8, 0.82, 0.84, 0.86, 0.88, 0.9, 0.92, 0.94, 0.96, 0.98, 1 or any point value in the range of the above two point values. The sphericity of the silicon-carbon material is at a higher level, which can inhibit the fragmentation of the silicon-carbon material to a certain extent, which is beneficial to reduce the consumption of the electrolyte. At the same time, it can avoid the problem of excessive consumption of the electrolyte due to excessive concentration of stress and strain in the local area caused by the excessive sphericity of the silicon-carbon material. It can also avoid the large difference in lithium ion migration speed in different areas of the material surface caused by the uneven SEI film, which further aggravates the problem of uneven stress and strain.
[0076] Exemplarily, a method for testing the sphericity of a silicon-carbon material may include the following steps: analyzing the image of each particle in the SEM photograph of the composite material at a certain magnification (e.g., 2500 times) by using image processing software (e.g., Image Pro Plus) to obtain the circumference and area of each particle, and respectively calculating the circumference equivalent radius r1 and area equivalent radius r2 of each particle, then the sphericity of each particle is S=r2 / r1, and then the sphericity of each particle is quantitatively weighted averaged to obtain the average sphericity of the silicon-carbon material composite material.
[0077] In some embodiments, the positive electrode active material layer further includes a positive electrode active material, a conductive agent, and a binder.
[0078] In some embodiments, the positive electrode active material is selected from one or more of transition metal lithium oxide, lithium iron phosphate, lithium manganese iron phosphate, lithium manganese oxide, and lithium-rich lithium manganese oxide; the chemical formula of the transition metal lithium oxide is Li (1+x) Ni y Co z M (1-y-z) O2, wherein -0.1≤x≤1; 0≤y≤1, 0≤z≤1, and 0≤y+z≤1; wherein M is one or more of Mg, Zn, Ga, Ba, Al, Fe, Cr, Sn, V, Mn, Sc, Ti, Nb, Mo, and Zr.
[0079] In some embodiments, the mass percentage of each component in the positive electrode active material layer is: 90wt%-99.2wt% of positive electrode active material, 0.4wt%-5wt% of conductive agent, and 0.4wt%-5wt% of binder.
[0080] Exemplarily, the mass percentage of the positive electrode active material in the positive electrode active material layer can be, for example, 90wt%, 91wt%, 92wt%, 93wt%, 94wt%, 95wt%, 96wt%, 97wt%, 98wt%, 99.2wt% or any point value in the range consisting of any two of the above point values.
[0081] Illustratively, the mass percentage of the conductive agent in the positive electrode active material layer can be, for example, 0.4wt%, 0.6wt%, 1wt%, 2wt%, 3wt%, 4wt%, 5wt% or any point value in the range consisting of any two of the above points.
[0082] Illustratively, the mass percentage of the binder in the positive electrode active material layer can be, for example, 0.4wt%, 0.6wt%, 1wt%, 2wt%, 3wt%, 4wt%, 5wt% or any point value in the range consisting of any two of the above points.
[0083] In some embodiments, the negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer coated on one side or both sides of the negative electrode current collector, and the negative electrode active material layer includes a negative electrode active material, a conductive agent, and a binder.
[0084] In some embodiments, the mass percentage of each component in the negative electrode active material layer is: 90wt%-99.2wt% of the negative electrode active material, 0.3wt%-5wt% of the conductive agent, and 0.5wt%-5wt% of the binder.
[0085] Exemplarily, the mass percentage of the positive electrode active material in the positive electrode active material layer can be, for example, 90wt%, 91wt%, 92wt%, 93wt%, 94wt%, 95wt%, 96wt%, 97wt%, 98wt%, 99.2wt% or any point value in the range consisting of any two of the above point values.
[0086] Illustratively, the mass percentage of the conductive agent in the positive electrode active material layer can be, for example, 0.3wt%, 0.4wt%, 0.6wt%, 1wt%, 2wt%, 3wt%, 4wt%, 5wt% or any point value in the range consisting of any two of the above points.
[0087] Illustratively, the mass percentage of the binder in the positive electrode active material layer can be, for example, 0.5wt%, 0.6wt%, 1wt%, 2wt%, 3wt%, 4wt%, 5wt% or any point value in the range consisting of any two of the above points.
[0088] In the present invention, the type of conductive agent is not specifically limited. For example, conventional conductive agents in the art can be selected, and the types of conductive agents include but are not limited to at least one of conductive carbon black, acetylene black, Ketjen black, conductive graphite, conductive carbon fiber, carbon nanotubes, and metal powder.
[0089] In the present invention, the type of binder is not specifically limited. For example, conventional binders in the art can be selected, and the types of binders include butadiene styrene rubber emulsion, polytetrafluoroethylene emulsion, sodium carboxymethyl cellulose, sodium alginate, polyvinyl alcohol, polyacrylic acid, lithium polyacrylate, sodium polyacrylate, at least one of carboxylated chitosan.
[0090] In some embodiments, the electrolyte may further include other solvents, lithium salts, and additives.
[0091] In the present invention, the type of the other solvent is not specifically limited, and can be selected from commonly used carbonates and carboxylates, such as ethylene carbonate (EC), fluoroethylene carbonate (FEC), propylene carbonate (PC), diethyl carbonate (DEC), ethyl propionate (EP), propyl propionate (PP), dimethyl carbonate (DMC), ethyl methyl carbonate (EMC), methyl propionate (MP), methyl butyrate (MB), ethyl acetate (EA), propyl acetate (PA) One or more.
[0092] In some embodiments, the mass proportion of the other solvents in the electrolyte is 30 wt%-80 wt%, for example, it can be 30 wt%, 35 wt%, 40 wt%, 45 wt%, 50 wt%, 55 wt%, 60 wt%, 65 wt%, 70 wt%, 75 wt%, 80 wt% or any point value in the range consisting of any two of the above point values.
[0093] In the present invention, the type of the lithium salt is not specifically limited, and can be selected from one or more of lithium hexafluorophosphate (LiPF6), lithium difluorophosphate (LiPO2F2), lithium hexafluoroantimonate (LiSbF6), lithium hexafluoroarsenate (LiAsF6), lithium bisfluorosulfonyl imide (LiFSI), lithium bistrifluoromethylsulfonyl imide (LiTFSI), lithium trifluoromethyl sulfonate, lithium di(trifluoromethylsulfonyl)imide, lithium di(pentafluoroethylsulfonyl)imide, tri(trifluoromethylsulfonyl)methyl lithium or lithium di(trifluoromethylsulfonyl)imide, lithium difluorooxalatoborate (LiDFOB), lithium difluorobisoxalatophosphate, lithium tetrafluoroborate (LiBF4), lithium di(difluorophosphoryloxy)difluoroborate, and lithium tetra(difluorophosphoryloxy)borate.
[0094] In some embodiments, the mass percentage of the lithium salt in the electrolyte is 12 wt%-28 wt%, for example, it can be 12 wt%, 14 wt%, 16 wt%, 18 wt%, 20 wt%, 22 wt%, 24 wt%, 26 wt%, 28 wt% or any point value in the range consisting of any two of the above points.
[0095] In the present invention, the type of the additive is not specifically limited, and one or more commonly used additives can be selected to further improve the cycle performance or high and low temperature performance of the battery, such as vinylene carbonate (VC), succinonitrile (SN), adiponitrile (AND), glutaronitrile (GN), hexanetrinitrile (HTCN), ethylene glycol bis (propionitrile) ether (DENE), glycerol trinitrile (TCP), tetravinylsilane (TVS), tris (trimethylsilyl) borate (TMSB), hexamethyldisilazane (HMDS), fluorobenzene (FB), triphenyl phosphite (TPPi), pentafluoroethoxy cyclotriphosphazene (PFPN) One or more.
[0096] In some embodiments, the total amount of the additive added in the electrolyte accounts for 8 wt%-15wt%, for example, it can be 8 wt%, 9 wt%, 10 wt%, 11 wt%, 12 wt%, 13 wt%, 14 wt%, 15 wt% or any point value in the range consisting of any two of the above point values.
[0097] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0098] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.
[0099] The present invention is described in detail below in conjunction with specific embodiments, which are used to understand but not to limit the present invention.
[0100] 1) Preparation of positive electrode The positive electrode active materials lithium cobalt oxide (LiCoO2), polyvinylidene fluoride (PVDF), SP (super P) and carbon nanotubes (CNT) are mixed in a mass ratio of 96:2:1.5:0.5, N-methylpyrrolidone (NMP) is added, and the mixture is stirred under the action of a vacuum mixer until the mixed system becomes a positive electrode active slurry with uniform fluidity; the positive electrode active slurry is evenly coated on both surfaces of the aluminum foil; the coated aluminum foil is dried, and then rolled and cut, and the cut positive electrode sheet is processed with a special roller containing a convex portion, wherein the convex portion has a height of 20 μm, a diameter of 3 mm, and a spacing of 2 mm, to obtain the desired positive electrode sheet, and the ratio of the projection area of the first convex portion on the positive electrode sheet to the unit area is m, and the value of m is shown in Table 1.
[0101] 2) Negative electrode preparation The negative electrode active materials artificial graphite, sodium carboxymethyl cellulose (CMC-Na), styrene-butadiene rubber, conductive carbon black (SP) and single-walled carbon nanotubes (SWCNTs) were mixed in a mass ratio of 94.5:2.5:1.5:1:0.5, deionized water was added, and the negative electrode active slurry was obtained under the action of a vacuum mixer; the negative electrode active slurry was evenly coated on both surfaces of the copper foil; the coated copper foil was dried at room temperature, then transferred to an oven at 80°C for drying for 10 h, and then cold pressed and cut to obtain the negative electrode sheet.
[0102] 3) Preparation of electrolyte In a glove box filled with argon (H2O < 0.1 ppm, O2 < 0.1 ppm), EC, PC, and compound A (Formula I-1) were mixed evenly, and then 16% of the total mass of the electrolyte was quickly added to fully dried LiPF6 to obtain the desired electrolyte. Among them, the mass ratio of EC, PC, and compound A is 10:10:80, and the mass ratio of compound A is 50% based on the total mass of the electrolyte. The mass ratio of EC and PC can be calculated using the above ratio.
[0103] The lithium-ion batteries obtained in the examples and comparative examples were subjected to a hot box test and a 4C cycle performance test, respectively.
[0104] Preparation of lithium-ion batteries The positive electrode sheet of step 1), the negative electrode sheet of step 2) and the separator are stacked in the order of positive electrode sheet, separator and negative electrode sheet, and then wound to obtain a battery cell; the battery cell is placed in an outer packaging aluminum foil, and the electrolyte of step 3) is injected into the outer packaging, and a lithium ion battery is obtained through vacuum packaging, standing, forming, shaping, sorting and other processes. The battery of the present invention has a charge and discharge range of 3.0-4.53V.
[0105] Performance Testing i) 5C cycle test The batteries obtained in the examples and comparative examples were discharged to 3.0V at 0.5C at 25°C. Then they were charged at 5C constant current to a voltage of 4.53V, then charged at a constant voltage at 4.53V to a current of 0.05C, left to stand for 5 min, and then discharged at 5C constant current to a voltage of 3.0V. This was a charge and discharge cycle. The discharge capacity of the first week of the test was recorded as x1 mAh, and the discharge capacity of the 500th week was recorded as y1 mAh; the capacity of the 500th week was divided by the capacity of the first week to obtain the cycle capacity retention rate R1=y1 / x1 of the 500th week.
[0106] ii) Hot box test At room temperature, the battery obtained in the embodiment and comparative example was charged to 4.53V at 1C constant current, left to stand for 60 min, and the appearance was checked and photographed. Then the temperature was raised to 132℃±2℃ at a rate of 3℃ / min±2℃ / min and maintained for 60 min. The sample was observed, and it was recorded as passing the test if there was no leakage, no smoke, no fire, and no explosion. 15 samples were tested for each embodiment or comparative example, and the pass rate of the hot box performance test was recorded.
[0107] iii) 4.58V cycle test The battery obtained in the embodiment and the comparative example was discharged to 3.0V at 0.5C at 25°C. Then it was charged at 5C constant current to 4.58V, then charged at 4.58V to 0.05C constant voltage, left to stand for 5 min, and then discharged at 5C constant current to 3.0V, which was considered a charge and discharge cycle. The discharge capacity of the first week of the test was recorded as x2 mAh, and the discharge capacity of the 500th week was recorded as y2 mAh; the capacity of the 500th week was divided by the capacity of the first week to obtain the cycle capacity retention rate R2=y2 / x2 of the 500th week.
[0108] iv) Lithium deposition test After 500T of cycling, the battery interface is disassembled to observe whether there is lithium deposition on the negative electrode. The criteria for judging lithium deposition on the negative electrode are: 1) no lithium deposition; 2) lithium deposition on the top, bottom and folds is recorded as slight lithium deposition; 3) lithium deposition on the entire surface is recorded as severe lithium deposition.
[0109] The Example 1-2 group and the Comparative Example 1-5 are carried out with reference to the Example 1-1, and the main differences are shown in Table 1, wherein the Example 1 group changes the ratio (m) of the total projected area of the first protrusion on the positive electrode sheet to the unit area. The Example 2 group changes the mass proportion (a) of the compound A in the electrolyte. For the Comparative Example 1, m is too small and is not within the protection scope of the present invention. For the Comparative Example 2, m is too large and is not within the protection scope of the present invention. For the Comparative Example 3, a is too small and is not within the protection scope of the present invention. For the Comparative Example 4, a is too large and is not within the protection scope of the present invention. For the Comparative Example 5, compound A is not added to the electrolyte.
[0110] Table 1 Note: “ / ” indicates that the corresponding parameter is not tested.
[0111] As can be seen from Table 1, as the ratio (m) of the total projected area of the first protrusion on the positive electrode sheet to the unit area increases, the rate of lithium ion release will increase, which can improve the fast charging performance of the battery. However, if m is too large, the lithium ions on the surface of the negative electrode material cannot be embedded in time, and lithium is precipitated on the negative electrode surface, which also slightly deteriorates the safety performance. The mass proportion (a) of compound A in the electrolyte gradually increases, which can improve the transmission rate of lithium ions in the electrolyte and improve the fast charging performance of the battery. However, if a is too large, it will also cause lithium ions on the negative electrode surface to aggregate, thereby causing dendrite growth and safety problems. Therefore, the present invention can improve the wettability of the electrolyte to the positive electrode material, increase the rate of lithium ion release, and improve the fast charging performance and safety performance of the battery by adjusting the ratio of the projected area of the first protrusion on the positive electrode sheet to the unit area and the proportion of compound A in the electrolyte.
[0112] Example 3 was carried out in accordance with Example 1-1, with the main differences shown in Table 2. In Example 3, DFEA (compound B) was further added to the electrolyte, and the mass proportion of DFEA in the electrolyte was changed (b).
[0113] Table 2 Note: “ / ” indicates that the corresponding parameter is not tested.
[0114] As can be seen from Table 2, further adding DFEA (compound B) to the electrolyte can improve battery performance and also improve the fast charging performance of the battery at high voltage. As the mass proportion of DFEA in the electrolyte increases, the transmission efficiency of lithium ions at the negative electrode interface increases first and then decreases, and the fast charging performance of the battery increases first and then decreases. Moreover, when the proportion of DFEA is too large, it will also cause dendrite growth and safety problems.
[0115] Example 4 was carried out in accordance with Example 3-1, with the main differences shown in Table 3. In Example 4, other types of compound B were further added to the electrolyte, and the mass proportion of the compound was kept the same as that of Example 3-1, i.e., b was 15%.
[0116] Table 3 It can be seen from Table 3 that further adding other types of compound B to the electrolyte and using it in combination with DFEA can further improve the fast charging performance and safety performance of the battery to a certain extent.
[0117] The fifth embodiment was carried out in accordance with the first embodiment, and the main differences are shown in Table 4. The fifth embodiment further optimized the drilling of the negative electrode structure, specifically including: laser-grooving the cut negative electrode sheet, and setting grooves on the entire surface of the negative electrode sheet, where the grooves are matrix grooves (such as Figure 3Schematic diagram), the groove width is 100 μm, the groove depth is 20 μm; the groove spacing is 2 mm, and the negative electrode sheet after laser treatment is cleaned and sliced to obtain the negative electrode sheet. And change the ratio (n) of the total projection area of the second concave portion on the surface of one side to the unit area.
[0118] Table 4 It can be seen from Table 4 that optimizing the perforation of the negative electrode can further improve the fast charging performance and safety performance of the battery. As the ratio (n) of the total projected area of the second recessed portion on the surface of the negative electrode sheet to the unit area increases, the lithium ion extraction efficiency of the negative electrode sheet is further increased, and the fast charging and safety performance are further improved. However, when n is too large, the structural stability of the negative electrode material decreases and the performance deteriorates.
[0119] Example 6 was carried out in accordance with Example 5-1, with the main differences shown in Table 5. In Example 6, compound C (Formula III-1) was further added to the electrolyte, and the mass proportion (c) of compound C in the electrolyte was changed.
[0120] Table 5 It can be seen from Table 5 that by further adding compound C to the electrolyte and adjusting the mass proportion (c%) of compound C in the electrolyte to satisfy 0.1≤c≤5, the safety and cycle performance of the battery can be further improved. However, when the mass proportion of compound C is too large, the interfacial impedance of the negative electrode will increase, thereby deteriorating the cycle performance of the battery.
[0121] Example 7 was carried out with reference to Example 6-1, with the main differences shown in Table 6. In particular, Example 7 changed the type of compound A in the electrolyte.
[0122] Table 6 It can be seen from Table 6 that using different types of compound A can produce similar effects and can improve the safety and cycle performance of the battery.
[0123] Example 8 was carried out with reference to Example 6-1, with the main differences shown in Table 7. In particular, Example 8 changed the type of compound C in the electrolyte.
[0124] Table 7 It can be seen from Table 6 that the use of different types of compound C can produce similar effects, which can improve the safety and cycle performance of the battery and improve the fast charging performance of the battery at high voltage.
[0125] Example 9 was carried out in accordance with Example 6-1, and the main differences are shown in Table 8. Specifically, Example 9 used artificial graphite and silicon-carbon material in the negative electrode active material, and changed the content of silicon in the negative electrode active material.
[0126] Table 8 Note: “*” indicates that the corresponding parameters are the same as those in Example 9-1.
[0127] It can be seen from Table 8 that by doping the negative electrode with silicon and increasing the lithium insertion sites, the fast charging performance of the battery can be further improved. However, when the silicon content in the negative electrode silicon-carbon material is too high, the safety performance will be deteriorated due to the large volume expansion of the negative electrode. The rupture of the SEI film will also consume the electrolyte to form a film, and will also deteriorate the cycle performance of the battery.
[0128] It should be noted that, in this article, the terms "comprise", "include" or any other variant thereof are intended to cover non-exclusive inclusion, so that the process, method, article or device including a series of elements includes not only those elements, but also includes other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise one..." do not exclude the presence of other identical elements in the process, method, article or device including the element. In addition, it should be pointed out that the scope of the methods and devices in the embodiments of the present application is not limited to performing functions in the order shown or discussed, and may also include performing functions in a substantially simultaneous manner or in reverse order according to the functions involved, for example, the described method may be performed in an order different from that described, and various steps may also be added, omitted, or combined. In addition, the features described with reference to certain examples may be combined in other examples.
[0129] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A lithium ion battery, characterized in that: The battery comprises a positive electrode sheet, a negative electrode sheet and an electrolyte; In the thickness direction of the positive electrode sheet, the positive electrode sheet comprises a first surface and a second surface arranged opposite to each other, the first surface is provided with a plurality of first protrusions at intervals, and the second surface is provided with a plurality of first recessed portions corresponding to the first protrusions; In a unit area of 1 cm×1 cm, the ratio of the total projection area of the first protrusion on the positive electrode sheet to the unit area is recorded as m%; m satisfies: 3≤m≤60; The electrolyte includes compound A, and the mass proportion of compound A is recorded as a% based on the total mass of the electrolyte; a satisfies: 5≤a≤70; The chemical formula of the compound A is shown in Formula I: (Formula I), Wherein, R1, R2, R3, R4, R5, R6, and R7 are independently selected from at least one of H, halogen-substituted or unsubstituted C1-C6 alkyl, halogen-substituted or unsubstituted C3-C6 cycloalkyl, halogen-substituted or unsubstituted C1-C6 alkoxy, halogen-substituted or unsubstituted C2-C6 alkenyl, and halogen-substituted or unsubstituted C2-C6 alkynyl.
2. The battery according to claim 1, characterized in that m satisfies: 20≤m≤40; and / or, a satisfies: 10≤a≤60; And / or, the compound A comprises at least one of the following compounds: (Formula I-1), (Formula I-2), (Formula I-3), (Formula I-4), (Formula I-5), (Formula I-6), (Formula I-7), (Formula I-8).
3. The battery according to claim 1, characterized in that The electrolyte further includes a compound B, and the compound B includes ethyl difluoroacetate; Based on the total mass of the electrolyte, the mass proportion of compound B is denoted as b%; b satisfies: 5≤b≤25.
4. The battery according to claim 3, characterized in that b and a satisfy: 0<a / b≤10; And / or, the compound B further comprises at least one of the following compounds: (Formula II-1), (Formula II-2), (Formula II-3), (Formula II-4), (Formula II-5), (Formula II-6), (Formula II-7), (Formula II-8), (Formula II-9), (Formula II-10), (Formula II-11), (Formula II-12), (Formula II-13), (Formula II-14).
5. The battery according to claim 1, characterized in that The first protrusion and / or the first depression satisfies at least one of the following conditions: (a) the height of the first protrusion is 3 μm-40 μm; and / or the depth of the first depression is 3 μm-40 μm; (b) the diameter of the first protrusion is 0.2 mm-8 mm; and / or the diameter of the first depression is 0.2 mm-8 mm; (c) the spacing between adjacent first protrusions is 0.2 mm to 8 mm; and / or the spacing between adjacent first depressions is 0.2 mm to 8 mm.
6. The battery according to any one of claims 1 to 5, characterized in that: In the thickness direction of the negative electrode sheet, the negative electrode sheet includes a third surface and a fourth surface arranged opposite to each other, and the third surface and / or the fourth surface are provided with a plurality of second recessed portions; within a unit area of 1 cm×1 cm, the ratio of the total projection area of the second recessed portions on the third surface or the fourth surface to the unit area is recorded as n%; n satisfies: 3≤n≤85.
7. The battery according to claim 6, characterized in that m and n satisfy: n>m; G=n / m, G satisfies: 1≤G≤4; G and a satisfy: 50≤a*G≤250.
8. The battery according to claim 6, characterized in that The second recessed portion satisfies at least one of the following conditions: (i) the width of the second recessed portion is 30 μm-4000 μm; (ii) the depth of the second recessed portion is 5 μm to 60 μm; (iii) The interval between the second recessed portions is 0.2 mm to 10 mm.
9. The battery according to any one of claims 1 to 5, characterized in that: The electrolyte further comprises a compound C, and the chemical formula of the compound C is shown in Formula III: (Formula III), Wherein, X1, X2, and X3 are independently selected from or , and at least one of X1, X2, and X3 contains an S group, A1, A2, A3, and A4 are independently selected from O, S, or an alkyl group connected to C, and at least one of A3 and A4 contains an O atom; Based on the total mass of the electrolyte, the mass proportion of compound C is denoted as c, where c satisfies: 0.1≤c≤5; The compound C comprises at least one of the following compounds: (Formula III-1), (Formula III-2), (Formula III-3), (Formula III-4), (Formula III-5), (Formula III-6), (Formula III-7), (Formula III-8), (III-9).
10. The battery according to any one of claims 1 to 5, characterized in that: The negative electrode sheet includes a negative electrode active material, and the negative electrode active material includes a silicon-carbon material; in the negative electrode active material, the content of silicon element accounts for 0.01%-70%; The silicon-carbon material satisfies at least one of the following conditions: 1) The Dv50 of silicon carbon material is 5 μm-15 μm; 2) The specific surface area of silicon carbon material is 0.3 m 2 / g-15 m 2 / g; 3) The sphericity of silicon carbon material is 0.8-1.
Citation Information
Patent Citations
Nonaqueous electrolyte compositions comprising cyclic sulfates and lithium borates
CN106537664A
Pole piece and battery cell
CN107681116A
High-voltage lithium cobalt oxide battery and preparation method thereof
CN116053456A
Battery
CN118867398A
Cited By
Electrode sheet, electrode assembly and battery
WO2026149505A1
